Analisis Persepsi Manfaat Akuntansi dan Kebutuhan Informasi Akuntansi Bagi Pelaku UMKM (Usaha Mikro, Kecil dan Menengah) di Kota Pontianak - B41109102, RENI KARINA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
This research aims to analysis the perception on the accounting benefit and requirement of accounting information for micro, small and medium (UMKM) enterprises in Pontianak City. The research method used by assosiative research, that is to analysis the influence of perception on accounting benefit and requirement of the accounting information to using accounting information for micro, small and medium (UMKM) enterprises in Pontianak City. Data collected to use the questionnaire measured with Likert scale and distributed to 100 of micro, small and medium (UMKM) enterprises in Pontianak City. The data gatherd than analyzed to use quantitative analysis that is multiple regression, F test, t test, and determination coefficient. The result of research indicate that micro, small and medium (UMKM) enterprises in Pontianak City to posses of positive perception on the accounting benefit and requirement of accounting information as to provider finance information. The perception on accounting benefit and requirement of accounting information in partial and simultance have an effect on significant to using accounting information for micro, small and medium (UMKM) enterprises in Pontianak City. The accounting benefit and requirement of accounting information give the big enough contribution to desire of micro, small and medium (UMKM) enterprises in Pontianak City to use the accounting information in the effort development in the future. Keywords: Accounting Benefit Perception, Accounting Information Requirement, Accounting Information Using, UMKM Enterprises